2020
DOI: 10.32718/nvlvet9914
|View full text |Cite
|
Sign up to set email alerts
|

Histological characteristics of Platelet-Rich Fibrin clots obtained under various modes of blood centrifugation

Abstract: Autologous products of the first and second generation, namely platelet-rich plasma and platelet-rich fibrin, are considered promising for regenerative medicine. They differ from each other in physical properties, as well as in the way they are obtained. The key procedure of all techniques is centrifugation; changing its parameters affects the biological properties of these biomaterials. The aim of the work is to determine and histologically characterize the area of concentration cells of autologous fibrin enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
1
0
1
Order By: Relevance
“…Histological evaluation revealed that the multiple use of I-PRF promoted better healing of the tendon. At the 6 th week observation, histological evaluation revealed better cell migration, proliferation and density as well as better arrangement and condensation of the fibers in the I-PRF group than A-PRF group while at the 12 th week observation showed higher condensation and arrangement of the fiber content with higher degree of collagen expression and lower cellularity indicating faster healing and regeneration of I-PRF group than A-PRF group and that was theoretically due to the continuous release of the GFs, cytokines and presence of leukocytes that was evident in the I-PRF because of the lowspeed centrifugation that prevented the push of these cells and permitted their presence in the I-PRF liquid during its preparation and that agreed with (Ghanaati et al 2014, Shevchenko andRublenko 2020).…”
Section: A B C Dsupporting
confidence: 70%
See 1 more Smart Citation
“…Histological evaluation revealed that the multiple use of I-PRF promoted better healing of the tendon. At the 6 th week observation, histological evaluation revealed better cell migration, proliferation and density as well as better arrangement and condensation of the fibers in the I-PRF group than A-PRF group while at the 12 th week observation showed higher condensation and arrangement of the fiber content with higher degree of collagen expression and lower cellularity indicating faster healing and regeneration of I-PRF group than A-PRF group and that was theoretically due to the continuous release of the GFs, cytokines and presence of leukocytes that was evident in the I-PRF because of the lowspeed centrifugation that prevented the push of these cells and permitted their presence in the I-PRF liquid during its preparation and that agreed with (Ghanaati et al 2014, Shevchenko andRublenko 2020).…”
Section: A B C Dsupporting
confidence: 70%
“…Recent studies proved the efficacy of I-PRF for enhancement of the healing process in different tissues (Wang et al 2018). Abd El Raouf et al (2019demonstrated for the first time the superior cartilage regeneration potential of I-PRF using the low-speed centrifugation concept in the early stages of cartilage repair while Shevchenko and Rublenko (2020) proved the higher concentration of platelets and leukocytes of the I-PRF in their study. This study aimed for evaluation of the efficacy of both I-PRF and A-PRF in enhancement of the healing of surgically treated AT rupture in dogs and compare the efficacy of the single administration of the A-PRF membranes with multiple injections of the I-PRF.…”
mentioning
confidence: 97%
“…Попередньо нами (Shevchenko et al, 2019;Shevchenko, 2020;Shevchenko & Rublenko, 2020), було проведено моніторингову оцінку технологій одержання тромбоцитарних мас для регенеративної медицини, їх гістологічну характеристику, встановлено динаміку гематологічних показників, макроморфологічної і рентгенологічної картини репаративного остеогенезу в кролів за використання тромбоцитарних концентратів та гідроксиапатитної кераміки, що засвідчили перспективність цього напряму.…”
Section: вступunclassified